Hubungan Intensitas Membaca Berita Vaksin Covid-19 Dan Intensitas Penerimaan Informasi Word Of Mouth Dengan Sikap Masyarakat Mengenai Vaksin Covid-19 - Novel C Damarjati, Dimas; Nugroho, Adi; Manalu, S. Rouli (Interaksi Online, 2024)
In 2020, the Covid-19 pandemic spread throughout the world. Various efforts have been made to resolve the pandemic, one of which is the Covid-19 vaccine. The Republic of Indonesia Governments made a statement that the public required to receive 2 doses of the Covid-19 vaccine and 1 booster dose. The emergence of the Covid vaccine has caused many pros and cons in society, given that the Covid vaccine is a new thing and there is a lot of confusing information about the vaccine. Although information and invitations for vaccines have been widely circulated, there are still people who refuse to be vaccinated. This study aims to determine the relationship between the intensity of reading Covid-19 news in the mass media and the intensity of receiving the Covid-19 Vaccine Word of Mouth information with public attitudes regarding the Covid-19 Vaccine. The theory used in this theory is the dependency theory of mass media effects and the theory of the buyer's information environment. The population in this study was the people of Central Java aged 18-25 years who were healty and ready to get the Covid-19 Vaccine. This study uses a non-random sampling method by means of purposive sampling. The results of the Kendall Tau-B analysis test show that there is a correlations between the intensity of the Covid-19 Vaccine news and the attitude of the Covid-19 Vaccine community, namely with a significance number of 0.224. Meanwhile, the results of the hypothesis test for the variable intensity of receiving Word of Mouth information with public attitudes regarding the Covid-19 Vaccine show a significant relationship of 0.449. The conclusion from the results of this study is that there is a relationship between reading the news and people's attitudes about the Covid-19 vaccine. This is because in times of crisis such as a pandemic which causes access to information from the media to be higher and information from the mass media can provide affective, cognitive, and behavioral effects for the audience. Then the word of mouth information is also related to public attitudes about vaccines. WoM information is believed to be easier to accept because there is no affiliation and occurs naturally, so WoM plays a role in disseminating information related to vaccines and is used as a basis for the community before using the Covid-19 Vaccine.